Lipid Peroxidation and Total Cholesterol in HAART-Naïve Patients Infected with Circulating Recombinant Forms of Human Immunodeficiency Virus Type-1 in Cameroon - Teto, Georges (Public Library of Science, 2013)
BACKGROUND: HIV infection has commonly been found to affect lipid profile and antioxidant defense. OBJECTIVES: To determine the effects of Human Immunodeficiency Virus (HIV) infection and viral subtype on patient’s cholesterol and oxidative stress markers, and determine whether in the absence of Highly Active Antiretroviral Therapy (HAART), these biochemical parameters could be useful in patient’s management and monitoring disease progression in Cameroon. For this purpose, we measured total cholesterol (TC), LDL cholesterol (LDLC), HDL cholesterol (HDLC), total antioxidant ability (TAA), lipid peroxidation indices (LPI), and malondialdehyde (MDA) in HIV negative persons and HIV positive HAART-naïve patients infected with HIV-1 group M subtypes. METHODS: We measured serum TC, LDLC, HDLC, plasma MDA, and TAA concentrations, and calculated LPI indices in 151 HIV-positive HAART-naïve patients and 134 seronegative controls. We also performed gene sequence analysis on samples from 30 patients to determine the effect of viral genotypes on these biochemical parameters. We also determined the correlation between CD4 cell count and the above biochemical parameters. RESULTS: We obtained the following controls/patients values for TC (1.96±0.54/1. 12±0. 48 g/l), LDLC (0. 67±0. 46/0. 43±0. 36 g/l), HDLC (105. 51±28. 10/46. 54±23. 36 mg/dl) TAA (0. 63±0. 17/0. 16±0. 16 mM), MDA (0. 20±0. 07/0. 41±0. 10 µM) and LPI (0. 34±0. 14/26. 02±74. 40). In each case, the difference between the controls and patients was statistically significant (p<0.05). There was a positive and statistically significant Pearson correlation between CD4 cell count and HDLC (r = +0.272; p<0.01), TAA (r = +0.199; p<0.05) and a negative and statistically significant Pearson correlation between CD4 cell count and LPI (r = −0.166; p<0.05). Pearson correlation between CD4 cell count and TC, CD4cell count and LDLC was positive but not statistically significant while it was negative but not statistically significant with MDA. The different subtypes obtained after sequencing were CRF02_AG (43.3%), CRF01_AE (20%), A1 (23.3%), H (6.7%), and G (6.7%). None of the HIV-1 subtypes significantly influenced the levels of the biochemical parameters, but by grouping them as pure subtypes and circulating recombinant forms (CRFs), the CRF significantly influenced TC levels. TC was significantly lower in patients infected with CRF (0.87±0.27 g/l) compared to patients infected with pure HIV-1 subtypes (1.32±0.68 g/l) (p<0.017). MDA levels were also significantly higher in patients infected with HIV-1CRF01_AE (0.50±0.10 µM), compared to patients infected with CRF02_AG (0. 38±0. 08 µM) (p<0.018). CONCLUSION: These results show that HIV infection in Cameroon is associated with significant decrease in TAA, LDLC, HDLC and TC, and increased MDA concentration and LPI indices which seem to be linked to the severity of HIV infection as assessed by CD4 cell count. The data suggests increased oxidative stress and lipid peroxidation in HIV-infected patients in Cameroon, and an influence of CRFs on TC and MDA levels.